Implementing IBM Spectrum Virtualize for Public Cloud on AWS Version 8.3.1 - Fincher, Jordan; Gadgil, Hemanand; Gucer, Vasfi; Shea, Jackson (IBM Redbooks, 2020)
IBM® Spectrum Virtualize is a key member of the IBM Spectrum® Storage portfolio. It is a highly flexible storage solution that enables rapid deployment of block storage services for new and traditional workloads, whether on-premises, off-premises, or a combination of both. The initial release of IBM Spectrum Virtualize for Public Cloud is now available on Amazon Web Services (AWS). This IBM Redpaper"!publication gives a broad understanding of the IBM Spectrum Virtualize for Public Cloud on AWS architecture. It also provides planning and implementation information about the common use cases for this new product. This publication helps storage and networking administrators plan, implement, install, modify, and configure the IBM Spectrum Virtualize for Public Cloud on AWS offering Version 8.3.1. It also provides a detailed description of troubleshooting tips